Economic Uncertainty and Fertility - Giray Gözgör; Mehmet Huseyin Bilgin; Peter Rangazas (Global Labor Organization (GLO), 2019)
In this paper, we conduct an empirical study of the effect of uncertainty on fertility. The precautionary motive for saving predicts that an increase in uncertainty increases saving by reducing both consumption and fertility. We use a new measure of uncertainty, the World Uncertainty Index, and focus on data from 126 countries for the period from 1996 to 2017. The empirical findings indicate that uncertainty shocks decrease the fertility rate. This evidence is robust to different model specifications and econometric techniques as well as to the inclusion of various controls.
Keywords: J13; D81; D14; E32; C33; 330; Fertility; Uncertainty; WUI Index; Precautionary Saving; Business Cycle; Panel Data Estimation Techniques